Dorsal Plating of Low-Energy Lisfranc Injuries: A Case Report. Issue 1 (February 2015) - Hsu, Albert; Moss, Lewis; Harris, Thomas G.
Surgically repairing acute Lisfranc injuries remains a difficult task, and the injury remains a challenging one for the treating surgeon. Although there are many proponents of acute arthrodesis for Lisfranc injuries, there remain a proportion of patients with low-energy trauma who may be best treated with open reduction internal fixation and joint salvaging procedures. Here, the authors present a case report and technique to anatomically fix Lisfranc injuries while preventing any concomitant articular damage in the process. They have found this to be a reliable and safe procedure in this demanding patient population. Levels: Level IV—Case Report